Regional climatic considerations for borderlands sustainability. Issue 1 (15th January 2013) - Gutzler, David S.
Abstract : Regional climate and its variability pose severe challenges to sustainability of ecosystems and human habitability in the U.S./Mexico border region. The region is semiarid, located far from oceanic sources of evaporated water. Its latitudinal position near the descending branch of the global atmospheric Hadley circulation means that cold season precipitation totals are suppressed relative to the average latitude of the winter storm track to the north. Furthermore, tree ring histories of climate variability demonstrate that the region is prone to shifts in the storm track that lead to very pronounced decadal variations in precipitation, which are manifested regionally as swings between severe droughts and pluvial periods. The El Niño‐Southern Oscillation in tropical Pacific Ocean temperature forces shorter term (year‐to‐year) shifts in the storm track. The border region is strongly affected by ongoing and projected century‐scale climate change, probably derived in large part from human‐caused increases in greenhouse gases. There is a very strong regional warming trend in recent temperature data, continued into the future in greenhouse gas‐forced model simulations of climate change. The warming trend modifies natural drought/pluvial precipitation fluctuations by enhancing evaporative losses and decreasing snowpack in mountainous regions to the north. These changes lead to projections of significantly diminished stream flow and drier surface conditions, thereby shifting the regional climate system farther toward aridity.